Time evolution of surface roughness in pipes due to mass transfer under different Reynolds numbers. (December 2016) - Wang, D.; Ewing, D.; Ching, C.Y.
Highlights: The time evolution of surface roughness in pipes is measured using a wall dissolving method. X-ray computed tomography (CT) is used to measure the surface topography. The roughness is characterized by the roughness height, length, width and density. The roughness height collapses well with time when normalized by the turbulent inner scales. The roughness height is strongly correlated to the wear due to dissolution. Abstract: Experiments were performed using a dissolving wall method to characterize the development of surface roughness in pipes at Reynolds number from 50, 000 to 200, 000. The test sections had a lining of gypsum that dissolved to flowing water in a closed flow loop. The tests were run over sequential time periods for each Reynolds number. At the end of each time period, the inner surface topography was measured using X-ray CT scans. Scallops are seen to initiate on the surface over time and then subsequently grow spatially and in depth with time. The surface was divided into smaller local areas and a scallop initiation time was introduced so that a common time datum from initiation could be used to characterize the time development of the roughness. The peak-to-valley roughness height was found to scale well with time when normalized by the turbulent inner scales. There is an initial period of slower growth rate in the roughness height, followed by a period of relatively higher growth rate. The growth of the integral length scale of the scallops is different, with an initial rapid growth followed by a much slower growth rate. The streamwise spacing of the scallops estimated from the density is approximately 1000 wall units as the scallops saturate the surface. There is a good correlation between the roughness height and the wear when normalized by the turbulent inner scales.